ANALISA TEMPAT PEMBUANGAN SEMENTARA (TPS) DI WILAYAH PETUK KATIMPUN KECAMATAN JEKAN RAYA KOTA PALANGKA RAYA (Analysis of temporary disposal places (tps) in the petuk katimpun area Jekan raya district, palangka city) - Linda Baktiani; Leti . (Huma Tabalien Jurnal (HTJ) Teknik Sipil, 2022)
Garbage is unwanted residual goods/material from the final product a certain process. Almost all human activities have the potential produce waste or waste, both organic waste, which is commonly called as wet waste and inorganic waste which is referred to as waste dry. The population in this study are 3 (three) Temporary Disposal Sites (TPS), namely: TPS Gang Anugerah, TPS Jalan AMD, and TPS Jalan Tjilik Riwut KM. 10 Petuk Katimpun, Jekan Raya District, Palangka Raya City. Study This method uses qualitative methods, where this method is a research used for research on the condition of natural objects. Technique data collection is done by way of interviews (interviews), observation (observation), literature study, and documentation. The data obtained in Fields are then selected and processed and presented in a relationship pattern between community participation in the Petuk Katimpun Region in management waste and solutions that are considered appropriate for waste management in the region the. The TPS volume of each TPS is the TPS Jalan Anugerah has TPS volume of 2.5 m3 ; TPS Jalan AMD has a TPS volume of 2.5 m3; and Jalan Tjilik Riwut KM.10 TPS has a TPS volume of 4.7 m3 The results of the study showed that the average volume of landfills per dayfrom each TPS, namely for TPS Jalan Anugerah, it has a volume daily average waste of 3.7 m3 ; AMD Street TPS has volume daily average waste of 3.7 m3 ; and TPS Jalan Tjilik Riwut KM.10 has an average daily waste volume of 6.5 m3 It shows that the volume of waste on average daily at each TPS is greater than than with the volume of its TPS area. That is, the TPS capacity that is currently availabl inadequate with the waste heap that is disposed of. Lack of awareness society in disposing of waste in the right place is also a factor in this garbage problem. This can be seen from the large amount of waste scattered around the polling stations. The right solution for handling this waste is by renewal of TPS in terms of size and shape as well as counseling to community about good and efficient waste management. Keywords: Garbage, Petuk Katimpun Area, Jekan Raya District Palangka Raya City, Waste Volume, waste Analysis, Management Method Garbage, Temporary Disposal Sites (TPS).